Ion exchange of lanthanum chloride and lewatit monoplus S 108 H resin - Zulkifli, Norazihan; Shoparwe, Noor Fazliani; Yusoff, Abdul Hafidz; Abdullah, Ahmad Zuhairi; Ahmad, Mohammad Norazmi (UMK Press, 2025)
Rare Earth Elements (REEs) are indispensable for numerous advanced technologies; however, their supply chain faces significant challenges due to geopolitical factors and the environmental impact of conventional mining methods. This study investigates the potential of ion exchange adsorption for the recovery and separation of REEs from a novel secondary source: carbonate precipitates derived from ionic clay leachates. Specifically, the performance of Lewatit MonoPlus S 108 H, a strong acid cation exchange resin, was evaluated through comprehensive batch adsorption experiments. The research encompassed kinetic and isotherm modelling. Kinetic studies revealed that the adsorption of lanthanum in chloride media at pH 2 followed the Pseudo-Second-Order model, indicating chemisorption as the rate-limiting step. Equilibrium data were best described by the Langmuir isotherm, with a maximum adsorption capacity (Qm) of 82.64 mg/g, suggesting monolayer adsorption on a homogeneous surface. The findings confirm the viability of Lewatit MonoPlus S 108 H for the selective recovery of rare earth elements from complex, secondary streams. This offers a sustainable pathway for the critical element supply.